2000
DOI: 10.1063/1.373783
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical analysis of unstable two-phase region and microscopic structure in wurtzite and zinc-blende InGaN using modified valence force field model

Abstract: A model to predict material characteristics of the InGaN ternary system, which is useful for blue and green light emitting and laser diodes, with respect to an unstable two-phase region in the phase field and the first neighbor anion–cation bond length is developed. The unstable region is analyzed using a strictly regular solution model. The interaction parameter used in the analysis is obtained from a strain energy calculation using the valence force field (VFF) model, modified for both wurtzite and zinc-blen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0
3

Year Published

2001
2001
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 18 publications
2
20
0
3
Order By: Relevance
“…Calculation results showed that the strain energy distributes around O atoms and that the total strain energy is lower in ZnSO than in ZnSeO. The strain energy of the ternary alloy, U, can be expressed by the following equation [8]:…”
Section: Resultsmentioning
confidence: 99%
“…Calculation results showed that the strain energy distributes around O atoms and that the total strain energy is lower in ZnSO than in ZnSeO. The strain energy of the ternary alloy, U, can be expressed by the following equation [8]:…”
Section: Resultsmentioning
confidence: 99%
“…The solid-solid miscibility characteristics of these semiconducting alloys have been studied, generally, assuming the regular solution model as the mixing model [1][2][3][4][5][6][7][8][9][10][11]. The interaction parameter (O) in the regular solution theory has been determined using various methods.…”
Section: Introductionmentioning
confidence: 99%
“…The parameters [6,7] used in this study are given in Table 1. Table 1 Parameters for the Valence Force Field model (Refs.…”
Section: Valence Force Field Modelmentioning
confidence: 99%
“…Takayama et al [6,7] have since refined the molecular model and have determined the miscibility characteristics and microstructure of other ternary and quaternary compound semiconductor alloys using the energy minimization approach of Ho and Stringfellow [3,4]. Adhikari and Kofke [8,9] used the molecular simulation approach to predict the miscibility diagram and local composition using the Valence Force Field (VFF) model for the InGaN, InAlN, GaAlN and InGaAlN alloys.…”
Section: Introductionmentioning
confidence: 99%